Lafaz Qalb, Shadr dan Fu’ad dalam Al-Qur’an - Suarni Suarni; Irda Mawaddah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2017)
The uniqueness of the Qur'an in terms of language is a miracle that has been shown to the Arab community since 15 centuries ago. Each vocabulary choice has its own language philosophy value. The subtlety of language can be seen in the balaghah and fashahah, both concrete and abstract in expressing and exploring the intended meaning. In the choice of words, the Qur'an sometimes uses several words that have the same meaning in Indonesian, so it appears that there are inconsistencies in the words it uses. This is the background of this discussion, precisely in the lafadz qalb, shadr, and fu'ad where the three words are often interpreted with one meaning, namely the heart. This research uses the maudhu'i method in the form of library research. In the Qur'an, the words qalb, shadr, and fu'ad have almost related meanings, but with different contexts and purposes, qalb is focused on things that are immaterial and psychic, spiritual qualities that are able to understand and determine good things. the bad of a soul because everything depends on the good or bad condition of the heart. Sadr called the chest is a container where the heart resides, so the use of the word sadr in the Qur'an is a kinayah for something that is in it, namely the heart. As for fu'ad, it is called an honest heart (conscience) and is a potential qalb, a place where a firm decision has been reached or something that has been bound, to be precise, fu'ad is a container of belief. Keunikan al-Qur'an dari segi bahasa merupakan kemukjizatan yang ditunjukkan kepada masyarakat Arab sejak 15 abad lalu. Setiap pemilihan kosakata mempunyai nilai falsafah bahasa tersendiri. Kehalusan bahasa terlihat dari balaghah dan fashahahnya, baik yang konkrit maupun abstrak dalam mengekspresikan dan mengeksplorasi makna yang dituju. Dalam pemilihan kata, al-Qur'an kadang menggunakan beberapa kata yang memiliki arti sama dalam bahasa Indonesia, sehingga tampak ada inkonsisten dalam kata-kata yang digunakannya. Inilah yang melatarbelakangi pembahasan ini, tepatnya pada lafadz qalb, shadr dan fu’ad yang ketiga kata tersebut sering diartikan dengan satu arti yaitu hati. Penelitian ini menggunakan metode maudhu’i berupa riset kepustakaan. Dalam al-Qur'an, lafaz qalb, shadr dan fu’ad mempunyai makna yang hampir berkaitan, namun dengan konteks dan tujuan yang berbeda, qalb tertuju pada hal-hal yang bersifat immateri dan psikis, sifat ruhani yang mampu memahami dan penentu baik-buruknya sebuah jiwa karena semua bergantung pada baik-buruknya keadaan qalb. Shadr disebut dengan dada adalah wadah di mana qalb bersemayam, sehingga penggunaan kata shadr dalam al-Qur'an merupakan kinayah bagi sesuatu yang ada di dalamnya yaitu qalb. Adapun fu’ad disebut sebagai hati yang bersifat jujur (hati nurani) dan merupakan potensi qalb, tempat di mana telah mencapai keputusan yang mantap atau sesuatu yang telah terikat, tepatnya fu’ad adalah wadah keyakinan.